Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Problem Based Learning (PBL) Berbantuan Media Berbasis Canva Pada Mata Pelajaran Pendidikan Pancasila di Kelas V SDN 01 Asam Kumbang Kabupaten Pesisir Selatan - Husna, Fidrathul; Iraqi, Hana Shilfia; Putera, Rafhi Febryan; Zuryanty, Zuryanty (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe how to improve student learning outcomes in Pancasila Education learning using the Problem Based Learning (PBL) model in class V SDN 01 Asam Kumbang Kabupaten Pesisir Selatan. This research is a Classroom Action Research (CAR) using qualitative and quantitative approaches, which is implemented in two cycles, namely cycle I (two meetings) and cycle II (one meeting) carried out in four stages, namely planning, implementation, observation and reflection. The subjects of this study were teachers and students of class V SDN 01 Asam Kumbang Kabupaten Pesisir Selatan with a total of 19 students, 8 boys and 11 girls. The results of this study showed an increase in the teaching module cycle I with an average of 85.41% (Good) and cycle II 95.83 (Very Good). Assessment of teacher activity cycle I with an average of 82.14% (Good) and cycle II 96.42% (Very Good). Assessment of student activity cycle I with an average of 82.14% (Good) and cycle II 96.42% (Very Good). Assessment of students in improving learning outcomes in cycle I obtained 74.94% and cycle II with an average of 85.76%. Based on these results, it can be concluded that the Problem Based Learning (PBL) model can improve learning outcomes of Pancasila Education in grade V.